Livestock innovations, social norms, and women’s empowerment in the Global South - Galiè, Alessandra; Najjar, Dina; Petesch, Patti; Badstue, Lone B.; Farnworth, Cathy Rozel (MDPI, 2022)
Livestock have strong empowerment potential, particularly for women. They offer millions of women in the Global South the opportunity to provide protein-rich foods for home consumption and sale. Livestock provide women with income and opportunities to expand their livelihood portfolios and can strengthen women’s decision-making power. Fully realizing livestock’s empowerment potential for women is necessary for sustainable livestock development. It requires, though, that gender-equitable dynamics and norms are supported in rural communities. We draw on 73 village cases from 13 countries to explore women’s experiences with livestock-based livelihoods and technological innovations. Our analysis follows a gender empowerment framework comprised of four interdependent domains—recognition of women as livestock keepers, access to resources, access to opportunities, and decision making as a cross-cutting domain—which must come together if women are to become empowered through livestock. We find improved livestock breeds and associated innovations, such as fodder choppers or training, to provide significant benefits to women who can access these. This, nonetheless, has accentuated women’s double burdens. Another challenge is that even as women may be recognized in their community as livestock keepers, this recognition is much less common among external institutions. We present a case where this institutional recognition is forthcoming and illuminate the synergetic and empowering pathways unleashed by this as well as the barriers that remain.